Efficient black liquor conversion to power and H2 based on process integration and exergy recovery. (October 2018) - Darmawan, Arif; Ajiwibowo, Muhammad W.; Aziz, Muhammad; Tokimatsu, Koji
Abstract: Hydrogen (H2 ) is considered as a clean energy carrier in the future with high efficiency and various utilization technologies. The H2 can be produced from biomass as primary energy source to reduce environmental impact. Currently, some projects are underway to achieve efficient conversion and reduce costs associated with H2 generation. High energy efficiency can be achieved by minimizing exergy loss through process integration and exergy recovery. In this study, co-production of H2 and power from black liquor (BL) is proposed based on process integration and exergy recovery. The proposed system consists of BL evaporation, gasification, syngas chemical looping (SCL), and power generation. The evaporation process employs exergy recovery using steam tube rotary evaporator. The effect of target moisture content on the evaporator performance is evaluated. Furthermore, the thermodynamics analysis of gasification is performed in circulating fluidized bed reactor based on Gibbs energy minimization. The SCL process comprises reducer, oxidizer and combustor and integrates with power generation. The result shows that the proposed integrated system can achieve higher efficiency of nearly 70%. In addition, the concentrated CO2 can be generated during the SCL process, avoiding additional cost for separation.